Development of Visionary Leadership Training Module for State Senior High School Principles - Sakinah Ubudiyah Siregar; Akmaluddin Akmaluddin; Siti Aisyah Hanim; Siti Lam'ah Nasution; Lili Syara (STAI Hubbulwathan Duri, 2024)
This study aimed to develop and evaluate a visionary leadership training module for principals at a public senior high school in Labuhan Batu. Specific objectives included creating the module, designing its content, assessing its feasibility, and gauging the principals' responses. The research employed a developmental approach, focusing on enhancing the principals' skills in vision articulation, decision-making, creativity, communication, motivation, empowerment, emotional intelligence, change management, role modeling, and understanding the organizational climate. With a confidence level of 95% and a significance level of 0.05, the study surveyed a total population of 84 individuals. The findings indicated the training module effectively fostered the desired leadership qualities. The module's development and its reception among the principals were both rated as very good, affirming its potential to foster visionary leadership in high school settings.